Effect of exogenous pulmonary surfactants on mortality rate in neonatal respiratory distress syndrome: A network meta-analysis of randomized controlled trials. (October 2015) - Zhang, Liang; Cao, Hong-Yi; Zhao, Shuang; Yuan, Li-Jie; Han, Dan; Jiang, Hong; Wu, Song; Wu, Hong-Min
Abstract: Background: The utilization of multiple natural and synthetic products in surfactant replacement therapies in treatment of neonatal respiratory distress syndrome (NRDS) prompted us to take a closer looks at these various therapeutic options and their efficacies. The purpose of our study was to evaluate the effects of six exogenous pulmonary surfactants (EPS) (Survanta, Alveofact, Infasurf, Curosurf, Surfaxin and Exosurf) on mortality rate in NRDS by a network meta-analysis. Methods: An exhaustive search of electronic databases was performed in PubMed, Ovid, EBSCO, Springerlink, Wiley, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang and VIP databases (last updated search in October 2014) to retrieve randomized controlled trials (RCTs) relevant to our study topic. Published clinical trials were screened based on the following inclusion criteria: (1) study design: RCTs; (2) interventions: treatment with Survanta, Alveofact, Infasurf, Curosurf, Surfaxin or Exosurf for NRDS; (3) study subject: infants with NRDS confirmed by clinical diagnosis; (4) outcome: the mortality rate of infants with NRDS. Statistical analysis was performed using Stata 12.0 software (Stata Corporation, College Station, TX, USA) and Comprehensive Meta-analysis (CMA 2.0) software. Results: From the 1840 studies initially retrieved through database searches, a total of 17 high quality RCTs were selected for this network meta-analysis. The selected studies included a combined total of 57, 223 infants with NRDS treated with various EPS (Survanta, 27, 017; Alveofact, 159; Infasurf, 20, 377; Curosurf, 20, 911; Surfaxin, 646; Exosurf, 1640). Network meta-analysis results showed that the mortality rates in NRDS infants treated with Alveofact, Infasurf, Curosurf, Surfaxin, Exosurf were not significantly different compared to Survanta (Alveofact: OR = 1.163, 95% CI = 0.645–2.099, P = 0.616; Infasurf: OR = 0.985, 95% CI = 0.777–1.248, P = 0.897; Curosurf: OR = 0.789, 95% CI = 0.619–1.007, P = 0.056; Surfaxin: OR = 0.728, 95% CI = 0.477–1.112, P = 0.142; Exosurf: OR = 0.960, 95% CI = 0.698–1.319, P = 0.799). Notably, the surface under the cumulative ranking curves (SUCRA) value in Surfaxin group was significantly higher than the other five groups (Surfaxin: 80.4%; Survanta: 37.0%; Alveofact: 24.4%; Infasurf: 40.0%; Curosurf: 73.9%; Exosurf: 44.2%), suggesting that infant mortality rate in Surfaxin group was the lowest among the six EPS groups. Conclusion: Our study demonstrated that Surfaxin could effectively reduce the mortality rate of infants with NRDS and may have a better efficacy in NRDS treatment, compared to Survanta, Alveofact, Infasurf, Curosurf and Exosurf.